1991
DOI: 10.1143/jjap.30.1489
|View full text |Cite
|
Sign up to set email alerts
|

Impurity Content Characterization of Brazilian Quartz Lascas

Abstract: Lattice impurities (Al, Li, Fe) free from the influence of cations in inclusion liquid were evaluated by atomic absorption spectrophotometry (AAS) in quartz lascas taken from 10 deposits with known localities in three states, Minas Gerais, Tocantins and Bahia. Levels of Al content and associated Li content depend on the localities of deposits. Quartz deposit regions with high Al content are composed of granite, gneiss, and pegmatite as surrounding rocks. It was concluded that the charge compensation for Al-Si … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
0
11
0
4
Order By: Relevance
“…Therefore those elements are found in trace amounts when quartz samples are analyzed (G€ otze, 2009;Miyoshi et al, 2005). Usually, the Al/Li ratio is particular from each quartz deposit and can indicate the conditions of crystallization (Iwasaki et al, 1991). G€ otze et al (2004) reported that the Al/Li for pegmatitic quartz is usually <10.…”
Section: Trace Elements and Fluid Inclusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore those elements are found in trace amounts when quartz samples are analyzed (G€ otze, 2009;Miyoshi et al, 2005). Usually, the Al/Li ratio is particular from each quartz deposit and can indicate the conditions of crystallization (Iwasaki et al, 1991). G€ otze et al (2004) reported that the Al/Li for pegmatitic quartz is usually <10.…”
Section: Trace Elements and Fluid Inclusionsmentioning
confidence: 99%
“…In addition, most of mines historically engaged in exportation frequently delivered the ore with irregular quality, i.e., with impurities and fluid inclusions exceeding the requirements of silica glass industry (Iwasaki et al, 1991;Santos et al, 2013). Furthermore, production was carried on using manual techniques, making it small and costly.…”
Section: Introductionmentioning
confidence: 99%
“…Não foi detectada a presença de P, Mg, Ca e Sr. A grande concentração de Cr, Fe e Ni medida apenas na variedade rósea pode ser explicada pela presença de inclusões sólidas microscópicas, de morfologia arredondada, observadas no resíduo da digestão ácida. Por sua vez, o Na, em concentração significativa na amostra de quartzo leitoso, pode ser proveniente de inclusões fluidas e, eventualmente, ocorrer como compensador de carga dos centros de Al (Iwasaki et al 1991).…”
Section: Resultsunclassified
“…The Al content, however, presents an abnormally low value. Most quartz resources, either hydrothermal, pegmatitic or diagenetic, usually contain more than 20 mg g À1 in Al (Santos et al, 2014;Müller et al, 2012;Suzuki et al, 2012;Li et al, 2010;Müller et al, 2007;Iwasaki et al, 1991). The content of Ge is also relatively low.…”
Section: Chemical Analysis Using Inductively Coupled Plasma Mass Specmentioning
confidence: 99%